Vaginal flora of first time urban family planning attendants in Accra, Ghana - Lassey, A.T.; Newman, M.J.; Opintan, J.A. (West African Journal of Medicine, 2006)
Objective: To determine the vaginal flora of first time urban Family Planning clients at Korle-Bu Teaching Hospital and to assess its implications for the contraceptive choices made. Design: A cross sectional study. Methods: A standardized questionnaire surveying the sociodemographic characteristics and the choice of Family Planning method was administered to 100 clients at the Korle Bu Teaching Hospital between March and September 2001. High vaginal and endocervical swabs were also taken during the inspection of the vagina and cervix using a sterile bivalve speculum. The specimens were transported in Amies transport medium to the Microbiology laboratory for processing. Results: The age range of the clients was 19-48 years with a modal age of 28 years. Ninety-six percent of them were married while 86% lived in urban slums. Sixty-three percent were sure of their last menstrual period. Potential pathogens were isolated from culture in 56% of the clients. Organisms causing bacterial vaginosis were the most prevalent in their genital tract. The intrauterine contraceptive device (IUCD) was the most common Family Planning method chosen, followed by the Norplant and the Depo-Provera injections. Potential pathogens were isolated from culture in 50% of those who chose the IUCD. Conclusion: Potential pathogens were isolated from culture in 56% of these first-time clients and organisms causing bacterial vaginosis were the most prevalent in the genital tract. It is suggested that Family Planning clients who screened positive for potential pathogens and opt for the IUCD should be considered for prophylactic antibiotics at insertion.
Keywords: Family planning attendants; Ghana; Vaginal flora